Pengaruh Pengetahuan, Motivasi Dan Komitmen Organisasi Terhadap Patient Safety Di Ruang Rawat Inap Rumah Sakit Umum Daerah Kabupaten Muna: The Effect of Knowledge, Motivation and Organizational Commitment on Patient Safety in the Inpatient Room of the Muna Regency General Hospital - Rahmayanti Tomasa; Samsualam Samsualam; Nurmiati Muchlis (Program Pascasarjana Universitas Muslim Indonesia, 2022)
Background; The success of implementing patient safety in health services from a hospital is reflected in the satisfaction of the patient or the patient's family. Therefore, strategic hospitals need to apply the principles or dimensions of service quality in accordance with customer needs and expectations. This study aims to determine the relationship between service quality and inpatient patient satisfaction at RSUD Kab. Muna. The general purpose of this study was to analyze the effect of the level of knowledge, motivation, and organizational commitment on the implementation of patient safety in RSUD Kab. Muna. Method: This research is a quantitative survey in the form of a cross-sectional approach. As what is examined in this study is the quality of health services in the inpatient unit of RSUD Kab. Muna. Results; The results showed that there was a relationship between knowledge of patient safety in the inpatient room at RSUD Kab. Muna with a value of p = 0.000 <0.05, there is a relationship between motivation to patient safety in the inpatient ward at RSUD Kab. Muna with a value of p = 0.000 <0.05, there is a relationship between organizational commitment to patient safety in the inpatient ward at RSUD Kab. Muna with p-value = 0.000 < 0.05. Conclusion: From the results of the study, it was found that of the 3 variables all related. To support better physical evidence, the hospital must pay more attention to hospital facilities so that it is more comfortable for every hospital visitor.